A Multicenter Retrospective Study Evaluating IL-5-Targeted Biologic Therapies for the Treatment of Asthma and Allergic Bronchopulmonary Aspergillosis in Adults With Cystic FibrosisTake-Home Points - Sameer Desai, PhD; Sophia Shen, MD; Zosia Gryz, BSc; Elizabeth Tullis, MD; Anne L. Stephenson, MD, PhD; Bradley S. Quon, MD, MSc (CHEST Pulmonary)
Background: Biologic therapies targeting T-helper cell type 2 (Th2) eosinophilic inflammation have been used for difficult-to-treat asthma and allergic bronchopulmonary aspergillosis (ABPA), but safety and efficacy data are limited in the cystic fibrosis (CF) population. Research Question: Are Th2 biologic therapies targeting eosinophilic inflammation effective and safe when used in adults with CF with asthma and/or ABPA overlap? Study Design and Methods: This was a retrospective multicenter study. Individuals with CF receiving Th2 biologic therapies for asthma or ABPA at 2 large adult CF centers between 2016 and 2021 were included. Treatment safety and effectiveness up to 12 months after biologic initiation were evaluated. Outcomes of interest included percent predicted FEV1 (ppFEV1), rate of change in ppFEV1, cumulative systemic corticosteroid (SCS) dose, and frequency of pulmonary exacerbations (PExs). Results: Forty adults with CF received Th2 biologic therapies targeting eosinophilic inflammation during the study period. A total of 38 were eligible for study inclusion, and all received IL-5-directed therapies (mepolizumab: n = 27, benralizumab: n = 11): 17 (45%) for asthma only and 21 for ABPA (55%) with or without asthma. No significant biologic-related adverse effects were observed. There was no statistical difference in ppFEV1 from baseline to 12-months postbiologic initiation, but the rate of change in ppFEV1 improved in the 12 months postbiologic vs prebiologic with a pre-to-post difference of 3.7% (95% CI, 1.2%-6.3%). SCS dose and frequency of PExs requiring hospitalization did not differ significantly in the 12 months before biologic vs after biologic initiation. Interpretation: Our results show that in adults with CF, anti-IL-5 biologic therapies were well tolerated and can improve rate of change in lung function, but there was no impact on SCS use or PEx frequency. Further study is needed to better define the role of Th2 biologics in the era of highly effective modulator therapy.